2021
DOI: 10.1002/ecs2.3363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shrub encroachment on soil aggregates and organic carbon vary in different grasslands in Inner Mongolia, China

Abstract: Widespread shrub encroachment in grasslands can lead to changes in soil aggregates and soil organic carbon (SOC), especially in deep soils. Soil aggregates physicochemically protect SOC and thus affect soil carbon sequestration. Characterizing the changes in soil aggregates and their organic carbon associated with shrub encroachment is critical for evaluating the ecological consequences of shrub encroachment in different grasslands. In this study, we investigated soil aggregates of various sizes and their asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…Zhibo et al (2020) showed that the contribution of aggregates > 0.25 mm to the organic carbon pool was signi cantly greater than that of aggregates < 0.25 mm. We found that the content of organic carbon and active carbon components of surface soil aggregates was slightly higher than that in deep soil, which was consistent with the research results of Zhu et al (2021). The content of SOC was the highest in the aggregates with > 2 mm particle size, and the aggregates with > 2 mm particle size also contributed the most to soil SOC.…”
Section: Effects Of Betula Platyphylla Invasion On Soil Organic Carbo...supporting
confidence: 89%
See 1 more Smart Citation
“…Zhibo et al (2020) showed that the contribution of aggregates > 0.25 mm to the organic carbon pool was signi cantly greater than that of aggregates < 0.25 mm. We found that the content of organic carbon and active carbon components of surface soil aggregates was slightly higher than that in deep soil, which was consistent with the research results of Zhu et al (2021). The content of SOC was the highest in the aggregates with > 2 mm particle size, and the aggregates with > 2 mm particle size also contributed the most to soil SOC.…”
Section: Effects Of Betula Platyphylla Invasion On Soil Organic Carbo...supporting
confidence: 89%
“…The dynamic change in soil organic carbon is not only dependent on the input of organic matter, but also closely related to the structure of soil aggregates (Zhu et al, 2021). Considering the composition ratio of organic carbon and active carbon components in the same particle size aggregate and the content of this particle size aggregate in soil comprehensively, the contribution rate of organic carbon and active carbon components to soil carbon in the aggregate can be comprehensively re ected (Wang et al, 2014).…”
Section: Effects Of Betula Platyphylla Invasion On Soil Organic Carbo...mentioning
confidence: 99%
“…The integrated rice-crayfish farming model affected the formation of soil aggregates compared to traditional paddy fields. Soil aggregates are a key factor affecting soil quality, and the content of aggregates at different grain sizes directly affects soil quality [24,25]. The present study showed that the integrated rice-crayfish farming model significantly increased the content of soil aggregates at >5 mm grain size.…”
Section: Distribution Of Soil Aggregatessupporting
confidence: 48%
“…ST, SA, LT, and other shrubs are widely distributed on the Zoige Plateau and are typical of the alpine shrub vegetation in the region, and they are the most influential of the shrubland types (Yang et al, 2017) and soil sampling depths (Chen et al, 2022). The effect of shrub invasion on soil is again determined by soil depth and grassland type, with deep soil organic carbon content showing higher levels in scrub than in grassland (Zhu et al, 2021). Most published studies have focused on the effects of climate (Gao et al, 2016) and grazing (Komac et al, 2013) on shrub encroachment, while the role of vegetation type and soil profile has rarely been considered (Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%